COMITE EDITORIAL - COMITE CIENTIFICO - Romero Guzmán, Nelson (Revista Entrelíneas, 2023)
Omar A. Mejía PatiñoRectorMabel Gómez MazorraVicerrector DocenciaDiego Alberto Polo ParedesVicerrector de Desarrollo HumanoMario Ricardo López RamírezVicerrector AdministrativoJonh Arteaga Jairo MéndezVicerrector de Investigación-Creación, Innovación, Extensión y Proyección SocialENTRELÍNEASREVISTA ESTUDIANTIL Carlos Arturo Gamboa B.Director ut.edu.co